ANALISIS PEMBAGIAN WARIS DARI HARTA BAWAAN MENURUT KUHPER & UUP 1974 - Mellisa Valencia; Khairani Bakri (Fakultas Hukum Universitas Trisakti, 2022)
Asset division is one of the effects of marriage. Assets that were acquired throughout the marriage by each party as well as assets that were inherited make up marital assets. When a death occurs, the marital assets turn into an inheritance that is transferred to the heirs. 1) How are inherited assets divided in the distribution of inheritance in accordance with the Civil Code and Law Number 1 of 1974 about Marriage? 2) In light of the Civil Code and Law Number 1 of 1974 regarding Marriage, is Decision Number 79/Pdt.G/2020/PN.Rap appropriate? This study is normative in character and has a descriptive and analytical tone. In addition to secondary data, this study also used primary and secondary legal sources. The data were analyzed qualitatively by deductively drawing conclusions. The conclusion is: 1) With the occurrence of death, inherited assets become inherited assets. So according to the Civil Code and the Marriage Law, related to the case, the inheritance as Hua Sin's inheritance was given to his wife as the heir of the first class. 2) Decision Number 79/Pdt.G/2020/PN Rap is not in accordance with Article 852 of the Civil Code jo. Article 35 to Article 37 of the Marriage Law.